Aprendizagem situada, comunidades de prática e inovação pedagógica - Pereira, Gorete (Científic@ - Multidisciplinary Journal, 2023)
Abstract This article reflects on situated learning as a result of interactions between learners and contexts. It starts from the concept of community and its relationship with the learning processes. The article defines community of practice and recognizes the social and situated nature of cognition. It recognizes that knowledge materializes in the form of situated experiences and not just in mental contexts. It addresses the study of students' learning, the type of participation in school activity and in the social contexts of intervention. It identifies pedagogical innovation in a disruptive perspective, which foresees profound changes in the traditional pedagogical relationship that understands the subject as co-builder of his knowledge.